1996
DOI: 10.1524/ract.1996.74.special-issue.15
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Neptunium(IV) Hydrous Oxide in Aqueous Solutions

Abstract: The solubility of neptunium(IV) hydrous oxide in water and NaC10 4 solutions was measured from over-and undersaturation directions at 25.0±0.2°C over a pH range of 5.30 to 13.7, in the presence of reducing agents (Na 2 S 2 04, metallic Fe or metallic Cu). Equilibration periods ranged from 1 to 119 days. All procedures were performed in a controlled atmosphere in a chamber containing high purity Ar (<1 ppm 0 2 ). Steady concentrations appeared to be reached within 28 days from the over-and undersaturation direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 5 publications
1
12
1
Order By: Relevance
“…Compared with the present case of U(IV), the solubilities of Th(IV) [13], Np(IV) [14][15][16] and Pu(IV) [17] have been reported to be constant at high pH, suggesting no predominant formation of penta-and hexahydroxide complexes up to pH 13-14. It is thus interesting to study different behaviors of actinides.…”
Section: Comparison With Literature Datacontrasting
confidence: 69%
“…Compared with the present case of U(IV), the solubilities of Th(IV) [13], Np(IV) [14][15][16] and Pu(IV) [17] have been reported to be constant at high pH, suggesting no predominant formation of penta-and hexahydroxide complexes up to pH 13-14. It is thus interesting to study different behaviors of actinides.…”
Section: Comparison With Literature Datacontrasting
confidence: 69%
“…Figures 4 and 5 present similar comparisons of the predicted solubility curves with the experimental results of Np(IV) [29][30][31][32] and Pu(IV), 15,[33][34][35][36] Rai et al 27) As shown in Figs. 4 and 5, the predicted solubility curves are again consistent with the experimental data in acidic region.…”
Section: Speciessupporting
confidence: 62%
“…In the experiments for Np(IV), a Np(IV) stock solution was prepared as 22 mol m −3 (2.2 × 10 −2 M or 1.36 × 10 11 Bq m −3 ) 237 Np(IV) dissolved in 10 3 mol m −3 (1 M) HCl [14]. The starting solutions were prepared under a controlled Ar atmosphere (< 1 ppm O 2 ) and added with Na 2 S 2 O 4 to eliminate the oxidation of Np(IV) by atmospheric O 2 .…”
Section: Methodsmentioning
confidence: 99%